Circulating γδT-lymphocytes subsets in patients with inflammatory bowel diseases - Tsekhanovich, Dmitry; Nizheharodava, Darya; Starastsin, Andrey; Dybau, Aleg; Vorobei, Alexander; Zafranskaya, Marina (Journal of the Belarusian State University. Ecology, 2023)
Due to the high growth of inflammatory bowel diseases (Crohn’s disease and ulcerative colitis) with unfavorable environmental factors in the background, studies of immunopathogenetic mechanisms including T-cells response resulted in gastrointestinal tract damage are of immediate interest. γδT-lymphocytes are of particular importance as their role in the dysregulation of the innate and acquired immune response to commensal bacteria in genetically susceptible people has not yet been fully studied. This paper presents the quantitative and functional parameters of γδT-lymphocytes in patients with Crohn’s disease and ulcerative colitis, indicating an enhancement of immunological surveillance in inflammatory bowel diseases. The increase of the cytotoxic and activation phenotype expression in circulating γδT-lymphocytes as well as a redistribution of their composition with dominating of tissue-resident cells subsets were revealed in patients what may be key links in the immunopathogenesis of Crohn’s disease and ulcerative colitis. The established correlations with the severity of diseases allow to consider the use of phenotypic and functional γδT-lymphocytes features as diagnostic and prognostic markers for the development of autoimmune inflammation as well as for a differential diagnosis of gut autoimmune pathology. While γδT-lymphocytes themselves can be used as a therapeutic target in the development of new protocols for the pathogenetic therapy of inflammatory bowel diseases.
Keywords: inflammatory bowel disease; autoimmune pathology; environmental factor; γδT-lymphocytes; flow cytometry